United States and Mexico : ties that bind, issues that divide - Aguila, Emma (Rand Corporation monograph series, 2012)
Despite geographical closeness and many shared economic interests, the United States and Mexico remain wary of one another. Policies designed to curtail the number of Mexican immigrants entering into the United States, a 700-mile-long border fence between the two countries, an increasing illegal drug trade, and continually troubled trucking legislation have somewhat eclipsed the North American Free Trade Agreement's (NAFTA's) cooperative scope. Additionally, the current international economic crisis has put any positive renegotiations between the United States and Mexico on hold. However, to ensure that the economic and political relationship between the two countries is as mutually beneficial as it is sustainable, it is critical that Mexico and the United States reiterate their commitment to their important relationship. This book focuses on how the alliance between the United States and Mexico can be made stronger, combining approaches from economics, demography, and sociology, discussions with U.S. and Mexican policymakers, reviews of published work, and results from opinion surveys. Whether relations between the two countries improve or deteriorate depends on the policies adopted by the current U.S. and Mexican administrations. New leaders in both countries are in a position to tackle common interests and take advantage of new opportunities without the baggage of past missteps and suspicions.--Publisher description.